Noise as a Harmful Production Factor (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
to acquaint students with the impact of industrial noise on the body, its regulation, measures to prevent the impact on the body of workers, noise measuring equipment, as well as methods for studying the effect of noise on the body.